The Existence of the Sharia Court in the Mechanism of Legal Integration in Aceh - Sri Dwi Friwarti; Ida Rahma; Budi Handoyo (IAIN Padangsidimpuan, 2021)
The presence of the Sharia Court in Aceh Province has further strengthened the authority to implement Islamic law in this province. However, there are several things that must be considered so that the rule of law can be realized namely: structural, substantial and cultural aspects. Law enforcement will work if these three aspects are carried out continuously. Nevertheless, there are still a number of legal experts and legal practitioners who have not been able to accept the delegation of authority for criminal cases (jinayat) to the Sharia Court. In fact, the presence of the sharia court as a component of the legal integration mechanism in Aceh. This study will address this issue by examining many regions in Southwest Aceh, including the Syar'iyah Courts of Tapak Tuan, Meulaboh, and Calang, as well as the Province, which serves as the delegation of appeal cases. After all, this research encourages the Sharia Courts to work closely with government stakeholders to provide information and disseminate authority